Pola Komunikasi Antara Guru Dan Santri Dalam Pembinaan Kedisiplinan Hafalan Al-Qur’an - Muslim, Akbar (Universitas Brawijaya, 2023)
Each communication has its own pattern in its implementation. This pattern of communication is important to know so that interactions that occur between individuals take place effectively. Errors in communication patterns can lead to less effective messages received by the communicant. Therefore, it is important to know the communication patterns used by teachers and students in carrying out learning, especially when memorizing the Al-Qur'an. This study aims to determine the pattern of communication used between teachers and students in fostering the discipline of memorizing the Al-Qur'an by taking the case study of Tpq Al-Mubarok, Sukamandi Baru Hamlet, Lenek Baru Village, Lenek District, East Lombok Regency. This research uses descriptive qualitative method. Data collection techniques are carried out by means of observation, interviews, and documentation. Data analysis techniques were carried out using the Miles and Huberman models. In testing the validity of the data, researchers used triangulation of sources and techniques. The results showed that the communication patterns used by teachers and students in fostering the discipline of memorizing the Qur'an TPQ Al-Mubarok were circular, wheel, and star communication patterns. This circular communication pattern is shown by the feedback given by the students to their teachers. The wheel communication pattern is shown by the teacher being able to communicate with the students at any time. While the pattern of star communication can be seen from each student who can communicate with one another.